(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the reforms implemented in the processes of admission to higher education institutions in the Republic of Uzbekistan. In the early years of independence, there were problems with admission to higher education due to shortcomings in the entrance exams. In the period after 2017, information was also provided about the progress made in ensuring transparency in the entrance exams. Changes related to the activity of the State Test Center (now the Knowledge and Skills Assessment Agency) were also studied. In particular, the introduction of the "compulsory" subject block in the entrance exams, certification systems for foreign languages ​​and subjects, and the Rasсh method were discussed. In addition, the essence of the changes implemented in recent years based on the study of foreign experience is also explained. The existing systems related to the existing admission processes at the international level were studied, and the possibilities of their implementation in Uzbekistan were also analyzed. Recommendations are also made for creating systems similar to some types of exams in foreign experience. The shortcomings and problems of the reforms implemented in this area were also discussed.